Digital citizenship and European Information Society. A critical analysis (Andamios, Revista de Investigación Social, 2012)
Today, the term Knowledge Society refers to a new social mediation and regulation framework that plays a significant role in framing comprehensive development policies. The European Union (EU) is planning, to follow this trend, new ways of governing built on participation and on the positive outcome deriving from the action of information and communication technologies (ICTs) on the urban scenario. This paper reviews some of the projects already set up by the European Commission as part of the Lisbon Agenda, conducting a critical inquiry on the Agenda´s conceptual framework and implied strategic planning with regard to digital citizenship; while, at the same time, we will explore on the nature of public discourse attached to e-Government in Europe as shown from the evidence of recent experience for the past five years.
Keywords: Digital citizenship; European Information Society (EIS); participation; local development; communication policies